Proceedings of the 17th ACM International Conference on Multimedia 2009
DOI: 10.1145/1631272.1631356
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual quality assessment based on visual attention analysis

Abstract: Most existing quality metrics do not take the human attention analysis into account. Attention to particular objects or regions is an important attribute of human vision and perception system in measuring perceived image and video qualities. This paper presents an approach for extracting visual attention regions based on a combination of a bottom-up saliency model and semantic image analysis. The use of PSNR (Peak Signal-to-Noise Ratio) and SSIM (Structural SIMilarity) in extracted attention regions is analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 4 publications
1
55
0
Order By: Relevance
“…However, Liu et al [10] reported that visual attention can be beneficial for two objective image quality metrics based on "ground truth" visual attention data from an eye-tracking experiment on natural images. We also found that visual attention detection can improve the accuracy in predicting video quality with general degradation [8] and image quality assessment in Digital Cinema (DC) scenario [11].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, Liu et al [10] reported that visual attention can be beneficial for two objective image quality metrics based on "ground truth" visual attention data from an eye-tracking experiment on natural images. We also found that visual attention detection can improve the accuracy in predicting video quality with general degradation [8] and image quality assessment in Digital Cinema (DC) scenario [11].…”
Section: Introductionmentioning
confidence: 81%
“…Ninassi et al [7] observed that integrating visual attention into spatial pooling schemes in image quality assessment is not always advantage based on their eye-tracking experiments. In our previous works, we also found that the performance improvement on image quality assessment using the Saliency model in [4] is marginally [8], and even a saliency attention based spatial pooling scheme has a negative impact on video quality assessment for packet loss streams [9]. However, Liu et al [10] reported that visual attention can be beneficial for two objective image quality metrics based on "ground truth" visual attention data from an eye-tracking experiment on natural images.…”
Section: Introductionmentioning
confidence: 83%
“…Conventional IQMs can be classified into three categories: structural information based [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], human perception/visual attention based [18][19][20][21][22][23][24][25][26][27][28], and information theoretical approaches [29,30]. In this section, conventional IQMs are reviewed.…”
Section: Related Workmentioning
confidence: 99%
“…Also visual attention based IQMs were developed [27,28]. Most existing IQMs do not take the human attention analysis into account.…”
Section: Human Perception Saliency and Visual Attention Based Iqmsmentioning
confidence: 99%
See 1 more Smart Citation